Question #ada15

1 Answer
Dec 9, 2016

Answer:

#x = -2# and #y = -3#

Explanation:

Step 1) Solve the second equation for #x#:

#x + y - y = -5 - y#

#x + 0 = -5 - y#

#x = -5 - y#

Step 2) Substitute #-5 - y# for #x# in the first equation and solve for #y#:

#3(-5 - y) - 2y = 0#

#-15 - 3y - 2y = 0#

#15 - 15 - 5y = 0 + 15#

#0 - 5y = 15#

#-5y = 15#

#(-5y)/(-5) = 15/(-5)#

#y = -3#

Now substitute #-3# for #y# in the solution to the second equation in Step 1) and calculate #x#.

#x = -5 - (-3)#

#x = -5 + 3#

#x = -2#